When consumers’ complaints fall into public domain: Negative E-WOM on social media - Langaro, D.; Loureiro, S. M. C.; Soares, A. (Exploring the power of electronic word-of-mouth in the services industry, 2020)
Despite previous studies having revealed that the content created by users in social media is predominantly positive, recent studies have challenged this understanding revealing by means of sentiment analysis the predominance of negative and neutral brand related content. The current chapter focuses on the new hybrid form of negative e-WOM in which individual´s complaints are directed at firms, which were originally limited to the domain of offline customer care teams. Thus, previous studies are reviewed from the area of crisis management and service recovery strategies with the intent to offer a relevant scope of theoretical propositions that may be considered by managers and researchers while preparing response strategies to deal with this new hybrid form of negative e-WOM. In total, eight theoretical propositions are presented and organized in three groups of guidelines associated to responses´ format, content, and context with fait-holders and hate-holders being considered as part of the negative e-WOM rhetoric.